A touchy subject: an assessment of cutaneous allodynia in a chronic migraine population - Mathew, Paul G (J Pain Res, 2016)
BACKGROUND: Cutaneous allodynia (CA) is a common feature of migraine, which has a complex underlying pathophysiology that is not well understood. In addition to pain, photophobia, phonophobia, osmophobia, nausea, and vomiting, CA can contribute to the overall disability caused by migraine. The presence of CA can be established via a validated questionnaire. Validated questionnaires and other tests are rarely performed in clinical practice. As such, current prevalence estimates for CA may be an underestimation. METHODS: Utilizing a validated questionnaire, we assessed the presence of CA in consecutive patients (n=44) presenting with chronic migraine at a tertiary headache center. RESULTS: CA appears to be quite prevalent, at ~90%, among female patients with chronic migraine. CONCLUSION: CA prevalence in chronic migraine may be underestimated in the literature, and larger studies may better demonstrate a more accurate estimate of its prevalence.